Degradation of Low-Density Polyethylene Greenhouse Film Aged in Contact with Agrochemicals - Caterina Picuno; Zoe Godosi; Gabriella Santagata; Pietro Picuno (Applied Sciences)
Plasticulture is a technique widely affirmed throughout Europe and the rest of the world that employs plastic material for protecting agricultural cultivations, e.g., soil mulching, low/middle tunnel covering, and greenhouse farming. Because of their effects on the sustainability of agricultural production, these materials present serious environmental drawbacks. Even if plastic recycling is a consolidated technical solution, several obstacles hinder the mechanical recycling of film used in plasticulture. Mostly, the degradation of its mechanical characteristics, due to aging and simultaneous contamination with agrochemicals used for fighting plant disease and ensuring crop health, plays a major hampering role. In the present paper, the results of laboratory tests on agricultural PE-LD plastic film for greenhouse covering, artificially aged for different lengths of time and treated with two different agrochemicals (fungicide and anti-aphid), are presented. The contamination with agrochemicals resulted in a considerable reduction in mechanical properties throughout the usage phase even if in samples that underwent twofold spraying, slower degradative kinetics were observed. In conclusion, based also on the measured changes in the Carbonyl Index value, it is doubtful that this plastic film would be included in a mechanical recycling process.